Patient and healthcare professional perspective on challenges in lipid profile management in dyslipidemia patients: Two separate cross-sectional surveys - Ramesh Bhandari, Madiwalayya Shivakantayya Ganachari (Journal of Applied Pharmaceutical Science, 2024)
Dyslipidemia is one of the major causes of cardiovascular ailments. Despite the fact patients with dyslipidemia continue to increase due to dependent on patient-related factors. To comprehensively explore patients’ knowledge, attitudes, and practices related to dyslipidemia, while also identifying challenges in lipid profile management among healthcare professionals. Two separate cross-sectional studies were conducted for 6 months (July–December 2021) in a tertiary care teaching hospital. The questionnaire (tool) for both surveys was prepared after a thorough review of the literature and then validated by a group of healthcare professionals. Eligible participants were enrolled after taking written informed consent. The current findings suggest poor knowledge, attitude, and practice of patients toward dyslipidemia and its management. Only 23.76% of healthcare professionals have attended seminars or continuing medical education on the management of dyslipidemia in the past year. It is surprising that only 37.62% of healthcare professionals surveyed know about the Lipid Association of India expert consensus statement on the management of dyslipidemia in Indians. Patient forgetfulness (66.37%) followed by the low education level of the patient (59.41%), side effects of the treatment (41.58%), high cost of the drugs (40.59%), and are the common reasons for noncompliance to the dyslipidemia therapy as reported by healthcare professionals. Patient-related factors contribute to major challenges in the management of dyslipidemia. The lack of awareness among healthcare professionals regarding dyslipidemia guidelines is attributed to the diversity in available guidelines and the limited applicability of Western-centric recommendations to Asian populations.
Keywords: Barriers, hyperlipidemia, management, pharmacist